A novel pH-responsive hydrogel-based on calcium alginate engineered by the previous formation of polyelectrolyte complexes (PECs) intended to vaginal administration - Ferreira, Natália Noronha [UNESP]; Perez, Taciane Alvarenga [UNESP]; Pedreiro, Liliane Neves [UNESP]; Prezotti, Fabíola Garavello [UNESP]; Boni, Fernanda Isadora [UNESP]; Cardoso, Valéria Maria de Oliveira [UNESP]; Venâncio, Tiago; Gremião, Maria Palmira Daflon [UNESP] (Taylor & Francis, 2017)
This work aimed to develop a calcium alginate hydrogel as a pH responsive delivery system for polymyxin B (PMX) sustained-release through the vaginal route. Two samples of sodium alginate from different suppliers were characterized. The molecular weight and M/G ratio determined were, approximately, 107 KDa and 1.93 for alginate_S and 32 KDa and 1.36 for alginate_V. Polymer rheological investigations were further performed through the preparation of hydrogels. Alginate_V was selected for subsequent incorporation of PMX due to the acquisition of pseudoplastic viscous system able to acquiring a differential structure in simulated vaginal microenvironment (pH 4.5). The PMX-loaded hydrogel (hydrogel_PMX) was engineered based on polyelectrolyte complexes (PECs) formation between alginate and PMX followed by crosslinking with calcium chloride. This system exhibited a morphology with variable pore sizes, ranging from 100 to 200 μm and adequate syringeability. The hydrogel liquid uptake ability in an acid environment was minimized by the previous PECs formation. In vitro tests evidenced the hydrogels mucoadhesiveness. PMX release was pH-dependent and the system was able to sustain the release up to 6 days. A burst release was observed at pH 7.4 and drug release was driven by an anomalous transport, as determined by the Korsmeyer–Peppas model. At pH 4.5, drug release correlated with Weibull model and drug transport was driven by Fickian diffusion. The calcium alginate hydrogels engineered by the previous formation of PECs showed to be a promising platform for sustained release of cationic drugs through vaginal administration.
Keywords: calcium alginate hydrogel; pH responsive hydrogel; polyelectrolyte complexes; polymyxin B; vaginal route